PERANCANGAN WISATA EDUKASI PROFESI DI KOTA TANGERANG SELATAN DENGAN KONSEP ARSITEKTUR HIGH-TECH - Novrianto, Dhanny; Subagya, Karya (MAESTRO, 2020)
Educational tourism is a travel activity undertaken to visit certain destinations to realize a situation of learning and learning process so that students actively develop their potential. A profession is a field of work that is based on a particular expertise education. Professional education tourism is an activity carried out to get to know a variety of professions carried out by adults such as doctors, police, pilots, firefighters, chefs, architects, captain, etc, High-Tech Architecture is an architectural flow that boils down to the idea of a modern architectural movement that magnifies the structure and technology of a building. Characteristics that become a reference for high-tech architecture are buildings made of synthetic materials such as metals, glass, and plastics.